American Silver Inflow and the Price Revolution in Qing China. Issue 1 (February 2016) - Zhao, Hongjun
Abstract: Employing panel data from the Northern China Plain for the period 1736–1911, this paper tests the so‐called price revolution hypothesis. It finds that American silver inflow played an important role in raising grain prices when factors such as weather and population are controlled. This role is verified in two dimensions: the quantity dimension of American silver inflow into China; the value dimension of silver relative to copper coin and to gold. This paper provides the first econometric test of the so‐called price revolution hypothesis in the 18th and 19th century China and deepens our understanding of the role of American silver inflow in late imperial times of China.